Evaluating technical and financial factors for commercialising floating offshore wind: A stakeholder analysis. Issue 11 (19th August 2022) - Moverley Smith, Ben; Clayton, Robert; van der Weijde, Adriaan Hendrik; Thies, Philipp R.
Abstract: Recently, floating wind has enjoyed much public and governmental attention and is commonly identified as a crucial next step on the route to net zero targets for many countries. However, there is currently a large gap between the scale and readiness‐level of devices in the water and the end‐of‐ the‐decade aspirational targets of many governments. To facilitate the expansion of the industry, a wider acceptance and agreement of the realistic potential of floating wind and the barriers to the sector's development is required, particularly over this crucial 10‐year period, something currently scarce in published literature. In this work, a stakeholder engagement was performed, with subsequent analysis of the results to quantify industry expectations and identify the predominant technical and financial concerns of key stakeholders. The presented results of the work serve to both provide a point of comparison and updated account of industry‐based expert views in the near term, with further scientific analysis investigating distinctions between different stakeholder types. Secondarily, the key concerns of industry were analysed and compared with a literature review of recent research effort within floating wind, providing a high‐level gap analysis. A knowledge of the gaps can inform future areas for academic enquiry, ensuring the future needs of industry and the focus of research is aligned.